2020
DOI: 10.1186/s12986-020-00489-1
|View full text |Cite
|
Sign up to set email alerts
|

High intensity exercise downregulates FTO mRNA expression during the early stages of recovery in young males and females

Abstract: Background: Physical exercise and activity status may modify the effect of the fat mass-and obesity-associated (FTO) genotype on body weight and obesity risk. To understand the interaction between FTO's effect and physical activity, the present study investigated the effects of high and low intensity exercise on FTO mRNA and protein expression, and potential modifiers of exercise-induced changes in FTO in healthy-weighted individuals. Methods: Twenty-eight untrained males and females (25.4 ± 1.1 years; 73.1 ± … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Depletion of m 6 A demethylase, FTO, led to impaired differentiation and fusion in vitro and impaired postnatal skeletal muscle development in vivo [ 21 ], and the overexpression of FTO promoted myoblast differentiation [ 22 ]. Similar to the results of our study, a dynamic pattern of FTO expression during myogenesis and different physiological processes in skeletal muscle has been observed [ 47 , 48 ]; however, the upstream regulation of this expression remains elusive. A recent study on FTO has shown that multiple metabolites can bind to FTO and regulate m 6 A levels [ 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…Depletion of m 6 A demethylase, FTO, led to impaired differentiation and fusion in vitro and impaired postnatal skeletal muscle development in vivo [ 21 ], and the overexpression of FTO promoted myoblast differentiation [ 22 ]. Similar to the results of our study, a dynamic pattern of FTO expression during myogenesis and different physiological processes in skeletal muscle has been observed [ 47 , 48 ]; however, the upstream regulation of this expression remains elusive. A recent study on FTO has shown that multiple metabolites can bind to FTO and regulate m 6 A levels [ 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings were also potentially interpreted by the epigenetic mechanisms possibly occurring during the intervention process. For example, individuals carrying the FTO risk allele might have a reduced risk of obesity after receiving physical activity interventions compared with those not receiving interventions, due to the downregulated expression of the FTO gene in skeletal muscle during the intervention process 50,51 . Take another instance, fruit‐based diets could downregulate the mRNA level of the FTO gene, 52 which might weaken the FTO –obesity association.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that males carrying the FTO risk allele lose more weight after a 12-week regular exercise [ 57 ]. An acute decreased skeletal muscle FTO mRNA expression was observed after high-intensity exercise by Danaher et al [ 14 ]. Most researchers focus on the reducing obesity risk caused by FTO gene polymorphisms under exercise, while there are few on its function.…”
Section: Discussionmentioning
confidence: 99%
“…FTO is highly expressed in the brain and likely involved in many nuclear RNA processing events, such as mRNA translation, splicing, and metabolism [ 11 , 13 ]. Previous study showed that highly intensive exercise decreases the skeletal muscle FTO mRNA [ 14 ]. However, the evidence on the effects of long-term exercise on FTO expression is scarce.…”
Section: Introductionmentioning
confidence: 99%